The Modernization of Islamic Educational Institutions: Answering Educational Challenges - Supriyanto Supriyanto; Fantika Febry Puspitasari; Agus Sriyanto (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Education is the life of civilization, meaning that only with education will an ideal civilization be realized. The ideal education will be challenging to realize while the management structured by the Principal as the supreme leader in the school is not of quality. Therefore, between quality education and quality education management must be an integral entity. The two components work hand in hand to produce qualified graduates. The head of SD Muhammadiyah 3 Assalam and SMK Muhammadiyah 1 Malang managed to modernize their school's management of his school so that the quality of graduates had high competitiveness. The management was named School Management, "No Box," which ultimately abandoned the old tradition of thinking towards more progressive thinking. Using a qualitative descriptive approach, the author explains the results of his research. It is expected that the reader is easy to understand. This study was obtained from the study library by utilizing the google scholar search engine to find relevant references, combined with interviews and observations, to obtain complete and detailed data. The results found that implementing the school's modernization management can boost graduate quality and improve the institutions' competitiveness of institutions. So the institution can be the primary choice of the public because it is considered able to answer parents and students.